This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
2^ x = 3^ y = 12^ z
Let it be equal to k . Then; 2^ x = 3^ y = 12^ z = k
So, this means
and we know that 12 = 2^2 X 3
So, 12 = k ^ z 1
=> 2^2 X 3 = k ^ z 1
[Instead of 2, we will put k ^ x 1 ]
[Instead of 3, we will put k ^ y 1 ]
( k ^ x 1 )^2 X k ^ y 1 = k ^ z 1
k ^ x 2 X k ^ y 1 = k ^ z 1
k ^ x 2 + y 1 = k ^ z 1
[Same base will be cut]
x 2 + y 1 = z 1
And as we can see, it is same as the next equation x q + k 1 = z 1
With 2 in place of q and y in place of k .
Hence k = y ; q = 2